Science-fiction féministe, des œuvres aux fans - Hélène Breda (ReS Futurae)
This article deals with the female and feminist science fiction fandoms from the second half of the twentieth century to the 2010’s. It aims to show that, even though SF has often been considered as a male-dominated cultural arec (from authors to audiences, and for character representations), many female readers and spectators appropriated the genre. Firstly, I put this subject into a historical perspective, by explaining that female SF fandoms were created in opposition to the male writers and fans communities which rejected them. As a consequence, the « fannes » had to organize somewhat secret activities and to produce their own derivative works, such as all-female SF fanzines. By doing so, they utilize the specific feminist potential of science fiction to gain agency and to convey some ideas relatecl to women’s right. In the second part of my study, through the example of fannish creations inspired by the books of Ursula K. Le Guin, Marion Zimmer Bradley and Margaret Atwood, I develop the hypothesis that such productions (fanfictions, fanarts, varions items) are both female empowerment and feminist activism tools.